Bright and Uniform Green Light Emitting InP/ZnSe/ZnS Quantum Dots for Wide Color Gamut Displays - Kim, Yongwook; Ham, Sujin; Jang, Hyosook; Min, Ji Hyun; Chung, Heejae; Lee, Junho; Kim, Dongho; Jang, Eunjoo (ACS applied nano materials, 2019)
There is an urgent demand to improve the efficiency and the color purity of the environment-friendly quantum dots (QDs), which can be used in wide color gamut (WCG) displays. In this study, we optimized the reaction conditions for the InP core synthesis and the ZnSe/ZnS multishell growth on the core. As a result, remarkable improvements were achieved in the photoluminescence quantum yield (PL QY, 95%) and the full width at half-maximum (fwhm, 36 nm), with perfectly matched wavelength (528 nm) for the green color in WCG displays. Injection of the phosphorus precursor at a mild temperature during the InP core synthesis reduced the size distribution of the core to 12%, and the shell growth performed at a high temperature significantly enhanced the crystallinity of the thick passivating layer. We also investigated the photophysical properties, particularly the energy trap distributions and trap state emissions of the InP-based QDs with different shell structures. The time-resolved and temperature-dependent PL spectra clearly indicated that the well-passivated InP/ZnSe/ZnS QDs showed nearly trap-free emissions over a wide temperature range (77–297 K). Also, the on- and off-time probability on single QD blinking and Auger ionization efficiencies also showed that these QDs were hardly affected by the surface traps.